Corporate governance and economic development identifying critical institutional reforms - Anna Lanoszka (London ; New York Routledge, Taylor & Francis Group, 2023)
"This book explores the links between different corporate governance systems and their impact on economic development. It focuses on how institutional reforms, legislative changes and codified measures have influenced performance at the firm and country level. Drawing on detailed cases from the UK, USA, China, India, Poland, Brazil, Russia and South Africa, this book takes a truly international and comparative approach to understanding the relationship between regulatory frameworks and economic development. This will be a valuable text for students and researchers of economic development, corporate governance, international political economy, and economic and business history"-- Provided by publisher.
Includes bibliographical references and index
Keywords: Corporate Governance